Functional improvement in individuals with chronic spinal cord injury treated with 4-aminopyridine: A systematic review - Paredes-Cruz, Martin; Grijalva, Israel; Martínez-López, Yoscelina Estrella; Guizar-Sahagún, Gabriel; Colín-Ramírez, Eloisa; Rojano-Mejía, David (Frontiers in Neurology, 2022)
Study design: a systematic review Objective: to provide current evidence on the efficacy of 4-aminopyridine (4-AP) in bringing about functional improvement in individuals with chronic traumatic spinal cord injury (SCI) Methods: The electronic databases, Medline (PubMed), Web of Science and SCOPUS, were systematically searched for relevant articles on the efficacy of 4-AP in treating SCI, from the first date of publication until May 2022. Full-text versions of all selected articles were selected and examined independently by two reviewers. Their methodological quality was rated using the Modified Jadad Scale, and risk of bias was assessed according to the RoB-2 test. Data extracted included the human model/type, the PRISMA assessment protocol and the results of each study. Descriptive syntheses are provided. Results: A total of 29 articles were initially identified, 10 of which were included after screening. Most of the studies reviewed reported some degree of improvement in one or more of the following parameters: motor, sensitive and sexual functions, sphincter control, spasticity, ability to function independently, quality of life, central motor conduction, pain and pulmonary function. Conclusions: This review confirms the efficacy of 4-AP in improving several conditions resulting from SCI; however, further research on this topic is warranted. Additional randomized clinical trials with 4-AP involving larger sample sizes are needed, as are consistent outcome measures that allow adequate data to be obtained for analysis, with a view to enhancing the benefits of treatment.